The production and transformation of space: Dismantling the space of artistic production - Şahin, Zümrüt (Graduate School, 2023)
This thesis explores the duality of the production of space by art and the production of art by space by asking the following questions: How is space involved in the process of artistic production? Does art also produce and transform space while being produced in/by it? Studio, which can be traced back to 16th-century artist inventories, originates from the Latin word studium and is defined as a room or a space where a painter or an artist works. However, this simple definition is insufficient to deliver the essence of the studio: a complex space of production and transformation occupied by the artist. A studio is a space of discovery, a space artist gets to reflect, a microcosm of an artist's work, a sanctuary, a revelatory, a laboratory, a social hub… The myth of the studio begins with the artist's self-portraits and their representations of the studio and later continues with photographers capturing artists in action in their studio. The aim of this thesis is to dismantle the atmosphere of the studio space and to raise a discussion on the spatial relations in the artist's studio. In this pursuit, an interdisciplinary approach to literature research has been followed comprehensively. Resources such as art history and art theory books, photographs, artist biographies, and autobiographies have been used very effectively, in addition to essential architectural theory and sociology publications which lay the foundation of this thesis, to gain more insight into the cosmos of the artist. As De Certeau states, "Space is a practiced place". Lefebvre declares that the perception, living, and production of space are through the body. Grosz explains space as being occupied by its inhabitants and how it is constantly in transformation, where objects, subjects, and their relations are structured and positioned. In the space of artistic production, also known as the artist's studio, space is produced as a result of the artist's actions and body movements while practicing art. The artist is the subject, and the artwork is the object which carries traces of its space and time. The artist's studio consists of many complex spatial relations that have been broken down into three focuses: Space and Practice, Space and Identity, and Space and Time. The section on space and practice focuses on the two far ends of the creative process, the dialectics of thinking and making. In some cases, while the studio is the space of absorption, an intellectual site, it is also the space for taking action and participating in craftsmanship. How this tension is reflected in the architectural space is found to be exciting and worthy of investigation. Secondly, the relations of space with the subject and the object within the studio require immense attention since it is an artist's highly private and personal space. As the artwork is being created, the identities of both the artist and the space are also being created and transformed simultaneously. Thirdly, the time aspect of space is highlighted as studio practices are the bodily encounters of the artist expanded into a timeframe, and time-space relations are essential for this subject. Finally, post-studio practices are introduced as a shift in the comprehension of the spaces that artists work in. The studio space undergoes changes over time, from modernism to postmodernism, eventually to the contemporary era. What it means to be in the studio has profoundly evolved and changed with the appearance of post-studio practices in art in the 1960s. As for contemporary studios, with many artists escaping their studios today, there are many variations of a studio and a more comprehensive selection of examples. Nevertheless, it is to be seen that the studio space is still a relevant topos and an essential space for contemporary artists. The spatial relations of the studio are revisited, this time encompassing contemporary studios and their extensions.
Mekânın üretimi ve dönüşümü: Sanatsal üretim mekânının sökümü
Thesis (M.Sc.) -- İstanbul Technical University, Graduate School, 2023
Keywords: Space; Practice; Importance of the Studio; Making space